Planejamento estratégico em uma instituição federal de ensino superior: estudo do planejamento estratégico decenal (2016-2025) do Instituto Federal da Paraíba - Oliveira, Jonathan Silva de (2020)
The present study has as main objective to analyze how the Decennial Strategic Planning (2016-2025) - PLANEDE - from the Federal Institute of Education, Science and Technology of Paraíba has been influencing the activities of managers in its first three years of effectiveness, from the perception of these managers, as well as information about their use of the PLANEDE electronic system. The research also proposes to describe the process of formulating, implementing and evaluating strategic planning and to identify the factors that are hindering its implementation. The research consists of a case study, predominantly qualitative and descriptive nature. Interviews were conducted with a public server of planning unit and with 28 managers at different levels, which were analyzed using Bardin's content analysis technique. Based on this information, it was possible to make inferences and conclude that, until then, PLANEDE has not been used as a management tool by most managers and that the implementation process has not been successful. One of the main explanations for this is the fact that PLANEDE is seen by most managers only as a computer system, with the purpose of recording information. That same software, which was supposed to assist the implementation of the plan, has proved to be one of its main barriers. As a product, a proposal for adjustments and improvements for PLANEDE was formulated, which will be handed over to the entity's management, which is expected to be used in its evaluation process.